PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP REAKSI PASAR: KINERJA KEUANGAN SEBAGAI VARIABELMODERATING - Arsani, Sunaini Hayati; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Thepurpose of this research is to test the influence of Good Corporate Governance which consists of independentcommissioner, managerial ownership, institutional ownership, and audit quality to the market reaction with thefinancial performance as the moderating variable which has been done by the manufacturing companies inIndonesia. The result of the research shows that GCG which is independent commissioner has an influence to themarket reaction, it means that the market accept the signal about the implementation of GCG in the companyand it overestimates by giving high premium for the share price of the company. Meanwhile, the managerialownership, the institutional ownership and the audit quality do not have any influence to the market reaction.The GCG in this case the independent commissioner, the managerial ownership, the institutional ownership andthe audit quality have influence to the financial performance whereas the managerial ownership does not haveany influence to the financial performance. The GCG in this case the independent commissioner has influence tothe market reaction through the financial performance, it means that the company a respond from the marketsince the investors who are going to purchase the shares are tend to be more interested in the company which hashigh profitability. Meanwhile, the managerial ownership, institutional ownership and audit quality variables donot have any influence to the market reaction even though it has been moderated by the financial performancevariable.Keywords: good corporate governance, market reaction, financial performance.